Empatia e preocupações psicológicas em cuidadores de pessoas idosas: revisão sistemática e efeitos do treinamento de empatia - Maximiano-Barreto, Madson Alan (2023)
Empathy is an important ability in social interactions and can be a predictor of or protector form the negative impacts of care, such as psychological concerns (e.g., burden, depression, anxiety and stress). Thus, empathy training has been developed with caregivers of older people to minimize the negative impacts of care. The present thesis is divided into three studies. The first two are systematic literature reviews and the third is an original study. Objectives: The main objective was to analyze the effects of empathy training on burden levels in caregivers of older people. The following were the specific objectives: i) identify the relationship between psychological harm, empathy and its domains (affective and cognitive); ii) identify empathy training models and the effects on psychological concerns; and iii) evaluate the effects and efficacy of empathy training on psychological concerns and empathy in caregivers of older people. Methods: Two systematic reviews were performed of articles retrieved from the Embase, LILACS, PsycInfo, Pubmed, Scopus and Web of Science databases. The search strategy for the first review was “Empathy AND Caregiver AND (Depression OR Burnout OR Anxiety OR Caregiver Burden OR Psychological Stresses)” and the strategy for the second review was “Empathy AND (Education OR Training OR Intervention) AND Caregiver”. No restrictions were imposed regarding language or year of publication. The third study was a randomized, double-blind, crossover, clinical trial with follow-up involving 30 paid and unpaid caregivers of older people who participated in five online encounters. Data were collected on empathy and domains, burden, the impact of providing care, depressive symptoms and psychiatric symptoms before, immediately after and after the intervention). Empathy was also investigated 15, 30 and 60 days after the intervention. Results: In the reviews, we found that higher levels of empathy affective were associated with more psychological concerns. Direct associations were found between affective empathy and depressive symptoms, anxiety and stress. In contrast, high levels of cognitive empathy were associated with fewer depressive symptoms as well as less stress and burnout syndrome. In the second review, empathy training methods were able to significantly increase levels of empathy and consequently reduce psychological concerns. In the clinical trial, the results revealed that online training was capable of diminishing psychological concerns (i.e., burden, impact of providing care and depressive symptoms) in caregivers of older people. Moreover, levels of cognitive empathy increased along the course of 15, 30 and 60 days after the intervention. Conclusions: The literature reports a direct association between affective empathy and psychological concerns. Higher levels of cognitive empathy can minimize psychological concerns. The literature revealed that empathy training for caregivers of older people can increase the levels of this ability, especially in the cognitive domain, as well as diminish psychological concerns. These results were confirmed by the empathy training conducted online.